ID 332 – Possible cause of autoimmune encephalopathy in epileptic patient. Issue 3 (March 2016) - Rassu, A.L.; Fois, C.; Sechi, E.; Piredda, R.; Murrighile, R.M.; Porcella, V.; Sechi, G.P.
Abstract : Objective: Autoimmune encephalopathies are life-threatening but treatable conditions. Recently, great interest has been taken in their early diagnosis. However, pathogenesis of so called seronegative forms it's not completely understood. Methods: A 28 years old man, with familiar history of migraine, short-stature and psychiatric disorders, presented to our clinic after three months of recurrent episodes of audio-visual hallucinations, déjà-vu, anxiety and mood changes. Twenty days after the beginning of valproate he developed progressive cognitive impairment, myoclonic jerks and tonic–clonic seizures. EEG revealed diffuse slowling of background activity with multifocal biemispheric sharp-waves. Results: Brain MRI and other imaging and laboratory tests for infectious, autoimmune or neoplastic conditions were negative. Liver function and ammonium levels were normal. Muscular biopsy was unremarkable. Relatives EEG pattern showed biemispheric multifocal slow abnormalities (mother and sister). A dramatic response after steroid, Ig therapy and concomitant discontinuation of valproate was observed. Genetic analysis for mitochondrial disorders are under way. Conclusions: The combination of suggestive clinical features and prompt response to immunomodulating therapy is sufficient for the diagnosis of autoimmune encephalopathies, even with negative diagnostic findings. Key message: Autoimmune encephalopathies remain a diagnosis of exclusion and alternative causes, like a toxic effect of valproate, have to be investigated.